Crisis and change in industrial relations in Central and Eastern Europe - Soulsby, Anna; Hollinshead, Graham; Steger, Thomas (Sage, 2017)
This article introduces the special issue on industrial relations in Central and Eastern Europe since the financial and economic crisis. Already dependent economically on funding from the west, and lacking the robust industrial relations institutions traditional in much of Western Europe, countries in the region were particularly vulnerable. However, there are important cross-national differences, and the strategies of key actors have significantly affected the outcomes.